The Hoopoe and the Child in Old Kingdom Art - McCorquodale, Kim.
Hoopoes are highly distinctive birds in Egyptian art. They have been attributed with a special link to children, and it has been claimed that in the Old Kingdom, a naked child who holds a hoopoe is the eldest son and the heir of the deceased. However, a broader examination of all children of the tomb owner and a larger corpus do not support these assertions. Hoopoes are held by both male and female adults as well as both male and female children. They are held by eldest and younger sons in almost equal numbers and in the majority of cases, where a younger son holds a hoopoe, the eldest son is present in the same scene but does not hold a hoopoe. It appears that hoopoes are just attractive birds that are held by both adults and children in much the same way as geese, ducks, pigeons, golden orioles, and other small birds. doi: http://dx.doi.org/10.5913/jarce.56.2020.a007